Peningkatan Strategi Lembaga Baznas Dalam Menarik Minat Masyarakat Untuk Membayar Zakat Mal Di Kecamatan Obi - Junaedi, Erina (Jurnal Ilmiah Wahana Pendidikan, 2025)
Abstrak ditulis dengan dua Bahasa, Inggris dan Indonesia, yang pertama berbahasa The purpose of this study is to analyze the outreach strategies implemented by BAZNAS Halmahera Selatan in Obi District to enhance community awareness of zakat. This study uses a descriptive qualitative approach, collecting data through interviews, observations, and documentation. The findings show that BAZNAS routinely conducts outreach through sermons, brochures, and direct communication with village officials, involving local religious leaders to improve public understanding. While effective, the strategy faces challenges, such as limited public understanding of zakat mal and BAZNAS’s resource constraints in staffing and facilities. Nonetheless, there is an increase in muzakki, particularly among government employees who are now more inclined to channel zakat through BAZNAS. To maximize these results, internal capacity building and strategic innovation are necessary to reach a broader audience and optimize zakat collection